NEW TRANSFORMATION OF ISLAMIC EDUCATION INSTITUTIONS AFTER THE ISSUE OF GLOBAL TERRORISM: TOLERANCE NARRATIVE STUDY OF CONSERVATIVE ISLAMIC BOARDING SCHOOLS IN INDONESIA - Abdul Malik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
Indonesian Islamic education institutions have thrived in the shadow of global terrorism for more than two decades. Global terrorism has now become the driving force behind the change of conservative Islamic education institutions. This study aimed to examine the new transformation of Islamic educational institutions, mainly orthodox boarding schools, prior to the issue of global terrorism. This study dove into the transformation through a shift in conservative boarding schools’ arguments related to the narrative of tolerance. This study was conducted through an empirical study using a qualitative-exploratory approach to several conservative Islamic boarding schools. This study suggested that traditional Islamic educational institutions in Indonesia are becoming more tolerant than in the past. There are three distinct types of tolerance: passive tolerance, active tolerance, and transformative tolerance.The pesantren has demonstrated tolerance thus far by essentially accepting differences and not disrupting others (passive tolerance). Currently, conservative pesantren engage in various social activities of tolerance, including assisting non-Muslims, fostering ties with other religious leaders, and permitting the construction of buildings of worship of other religions inside the Muslim community. Some of these elements are a small portion of the recently little-known active and transforming tolerance of conservative pesantren.